A supervision programme for social workers responsible for monitoring foster care placements - Malgas, Mantsepo Portia (North-West University, 2011)
A large number of children find themselves in foster care situations in South Africa with placements that have to be monitored by social workers. This is a demanding task, given the nature of foster placements and the heavy caseloads of social workers responsible for monitoring of foster placements. Although a wealth of information on social work supervision is to be found in the prevailing literature, no comparative volume of information is to be found on supervision in child welfare in particular. A model for supervision in this field must still be developed. In view of this and considering the supervisory role occupied by the researcher in Child Welfare South Africa, Free State, it was decided to embark on a research project investigating supervision in the field of child welfare, specifically with foster care social workers. Supervision in the field of child welfare is under researched and that a supervision model for this purpose should still be developed. The research results indicated that social workers monitoring foster care placements have large caseloads and that some of them receive supervision for too long. The supervision that they receive fulfils most of their needs, and that they found their supervisors very accessible. The most important learning needs were related to the Children's Act no.38 of 2005 as it applies to foster placements, and the submission of section 159 reports in time.
Thesis (MSc (Physiology))--North-West University, Potchefstroom Campus, 2013.